Ethics education of business leaders : emotional intelligence, virtues, and contemplative learning - Culham, Tom E. (Transforming education for the future, 2013)
Events on Wall Street and Main Street reveal that some business leaders make dramatically unethical self-serving decisions that ignore the public interest. How can business schools educate future business leaders to make ethical decisions? Unfortunately, most business schools fail in teaching ethical decision-making. They erroneously assume that such decision-making is primarily conscious and reason-based, reflecting the western cultural orientation toward science and logic.In this book, Thomas Culham cites neurological findings showing that unconscious processes and emotions play a much more significant role than reason in making ethical decisions. Culham urges business schools to teach a modified form of emotional intelligence, linked with research-supported contemplative practices from the great meditative traditions. This book details the author's ethics curriculum and explains its successful application at the Sauder School of Business at the University of British Columbia. This fascinating, interdisciplinary, and highly practical curriculum integrates philosophy (virtue ethics), Daoist thinking, psychology, and neuroscience. This curriculum intends to transform the way business schools teach decision making. Such an effort might just transform the way we do business.